Nanoparticles with a diamond-like structure and the inverse Hall–Petch law - Zakarian, D.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
For nanoparticles with a diamond-like structure, the inverse Hall–Petch law is obtained from first principles (a priori pseudopotential method). It is shown that the Hall–Petch coefficient depends on the crystal lattice parameters of nanoparticles.